Avaliação das interações entre potenciais inibidores da proteína di-hidrofolatoredutase do mycobacterium tuberculosise homo sapiens - Mecenas Filho, Marco Antonio (2019)
Tuberculosis is a disease transmitted by air, attacking mainly the lungs. It is caused by the pathogen Mycobacterium tuberculosis, which has a permanence or persistence ability within the host cells for a period, as well as achieved by the action of the immune system and can be activated. An important target for the treatment of this disease is the dihydrofolate reductase protein, as its inhibition leads to cell death. However, the human species also has this protein, so it is necessary that the drugs have a selectivity for the bacteria. Theoretical chemistry methods are used to aid in the search for new drugs and in this work we emphasize docking, which analyzes the stability of a ligand at the site of interaction in the dihydrofolate reductase proteins of Mycobacterium tuberculosis (MtbDHFR) and Homo sapiens (HuDHFR). Where it shows that little bulky compounds with groups withdrawn from electrons have greater selectivity for MtbDHFR. A mutant of the protein of the pathogen created, where it was shown that very voluminous compounds present difficulty in the active site of the protein caused by a possible steric effect.